2020
DOI: 10.1182/blood-2020-140482
|View full text |Cite
|
Sign up to set email alerts
|

In-Class Transition (iCT) from Parenteral Bortezomib to Oral Ixazomib Proteasome Inhibitor (PI) Therapy Increases the Feasibility of Long-Term PI Treatment and Benefit for Newly Diagnosed Multiple Myeloma (NDMM) Patients in an Outpatient Setting: Updated Real-World Results from the Community-Based United States (US) MM-6 Study

Abstract: Background Long-term PI-based treatment is associated with improved outcomes in MM. Nonetheless, prolonged therapy with parenteral PIs (e.g. bortezomib) can be challenging in the real world, with median duration of therapy (DOT) of 4-7 months. Barriers to this long-term approach may include the burden of repeated intravenous/subcutaneous administration, difficulty travelling to/accessing treatment centers (e.g. due to environmental factors, travel restrictions, social/family situations), patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In ASH 2020, although the final results of a real-world community-based US-MM6 Study 18 have not been published yet, positive updates have been reported. The bortezomib-based combination can rapidly reduce the tumor load after a few cycles, and when maximum benefits are reached, bortezomib can be switched to ixazomib.…”
Section: Updates Of Maintenance Strategiesmentioning
confidence: 99%
“…In ASH 2020, although the final results of a real-world community-based US-MM6 Study 18 have not been published yet, positive updates have been reported. The bortezomib-based combination can rapidly reduce the tumor load after a few cycles, and when maximum benefits are reached, bortezomib can be switched to ixazomib.…”
Section: Updates Of Maintenance Strategiesmentioning
confidence: 99%